Determination of the Perceptions of Health Professionals Working in the Operating Room with Regarding Occupational Health and Safety - Savuci, Yağmur; Yeşilyurt, Tugba Yesilyurt (My University, 2026)
Objective: This descriptive and cross-sectional study aimed to determine the perceptions of healthcare professionals working in the operating room regarding occupational health and safety. Methods: The study population consisted of 190 healthcare workers working in the operating room of a public hospital in Elazığ province, and the sample included 151 healthcare workers who voluntarily agreed to participate. Data was collected using the \"Personal Information Form\" and \"Occupational Safety Scale for Healthcare Personnel Working in the Hospital\". Results: The mean total score of the Occupational Safety Scale for Healthcare Personnel Working in Hospitals was 126.72 (35.46) indicating a low level. The highest score was obtained from the \"occupational diseases and complaints\" subscale, while the lowest score was obtained from the \"suitability of physical environment\" subscale. It was found that healthcare workers who graduated from a health vocational high school, had 16 or more years of professional experience, did not experience occupational accidents or diseases, and reported that the presence of a health and safety committee in the institution had a significantly higher perception of occupational safety Conclusion: The results suggest that health institutions should increase their efforts to raise awareness among healthcare workers about occupational health and safety. They should also determine the causes of occupational accidents and diseases and implement preventive measures.
Keywords: Occupational health and safety; Occupational disease; Occupational accident; Operating room